If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -1) = 9x + 3 Reorder the terms: 3(-1 + 2x) = 9x + 3 (-1 * 3 + 2x * 3) = 9x + 3 (-3 + 6x) = 9x + 3 Reorder the terms: -3 + 6x = 3 + 9x Solving -3 + 6x = 3 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -3 + 6x + -9x = 3 + 9x + -9x Combine like terms: 6x + -9x = -3x -3 + -3x = 3 + 9x + -9x Combine like terms: 9x + -9x = 0 -3 + -3x = 3 + 0 -3 + -3x = 3 Add '3' to each side of the equation. -3 + 3 + -3x = 3 + 3 Combine like terms: -3 + 3 = 0 0 + -3x = 3 + 3 -3x = 3 + 3 Combine like terms: 3 + 3 = 6 -3x = 6 Divide each side by '-3'. x = -2 Simplifying x = -2
| 1a=-5a | | 0.08(x-100)=83.5-0.07 | | 3n+4=57 | | 5y+10-y=29 | | f(x)=x^2-4x-44 | | -8(v+7)+8=-33-5v | | Y+5-9=10 | | 2=2.27-4 | | 2*(5-3)-3x=5 | | 5(-4)-6-7(-4)=2 | | -7+-10P*2+-9(-10P*2+1)= | | (3y+100)+(y+80)=180 | | -5-15+1=14y-32-y | | -5x-2-10=2-(-2+4) | | 75-2x=-15 | | 16+2f=22 | | 2b+4=b-3 | | 20b^2-136b-28= | | (3/4)x=(5/8) | | 4(5x-7)=56 | | X+1+1=6x-5x+2 | | .40x+.1=.60 | | N=-300+15N | | 5a+2+2a-7+4a=7 | | 6z+19=4z+19 | | -5x-2-10=2-(x+4) | | 85l=685 | | 3(X+1)=2X+24-X | | -3(y-7+3)+3=0 | | 6g+4(g)=1-g | | -x+x=91+7 | | X=-7y-10 |